Developing a new risk management-human governance (RMHG) framework on firm efficiency - Ting, Irene Wei Kiong; Darun, Mohd Ridzuan; Lee, Chia Kuang; Kweh, Qian Long (2019)
This study finds a nonlinear relationship between ownership concentration and R&D investments. Specifically, ownership concentration is positively related to R&D investments at a low level of ownership concentration; the relationship becomes negative when ownership concentration is at a high level. However, the impact of ownership concentration on R&D investments is lessened in family-controlled firms; that is, family control moderates the relationship between ownership concentration and R&D investments. Overall, this study suggests that the ownership concentration’s nonlinear impact on R&D investments differs between family-controlled firms and non-family-controlled firms.